1998
DOI: 10.1113/expphysiol.1998.sp004099
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and composition in rat pregnancy: effects of streptozotocin‐induced diabetes mellitus and insulin replacement

Abstract: SUMMARYA disturbed calcium homeostasis characterizes diabetic pregnancy. This study documents changes in bone mineral composition in diabetic pregnant rats and examines the effect of insulin replacement. Control pregnant (CP), diabetic pregnant (DP) and insulin-treated DP (DP1) rats were assessed for femoral calcium and magnesium content, bone mineral density (BMD) and the ratio of hypertrophic to maturing and proliferative cells in the femoral growth plate. DP rats showed a significantly (P < 0.01) lower body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…The present finding of reduced bone size and thereby reduced Ca content, but with maintained Ca concentration, corroborates previous reports of diabetes affecting bone development (Verhaeghe et al 1986, Tein et al 1998. The higher ratios of hypertrophic cells to proliferative cells in the growth plate found in the diabetic rat femurs in this study may be explained by a reduced local synthesis of mitogenic growth factors, such as insulinlike growth factor-I (Lazowski et al 1994).…”
Section: Figuresupporting
confidence: 81%
“…The present finding of reduced bone size and thereby reduced Ca content, but with maintained Ca concentration, corroborates previous reports of diabetes affecting bone development (Verhaeghe et al 1986, Tein et al 1998. The higher ratios of hypertrophic cells to proliferative cells in the growth plate found in the diabetic rat femurs in this study may be explained by a reduced local synthesis of mitogenic growth factors, such as insulinlike growth factor-I (Lazowski et al 1994).…”
Section: Figuresupporting
confidence: 81%
“…Some animal experiments revealed that low content of Ca, P, and Mg associated with the BMD decrease in diabetic osteoporosis [21,22], but it is not clear how the bone mineral element changes after insulin treatment. The aim of this study is to assess the correlation between the BMD and the mineral content after insulin treatment in STZ-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of different abnormalities indicating altered bone formation after inducing DM with streptozotocin (STZ) is well documented (Giglio and Lama, 2001;Hough et al, 1981;Tein et al, 1998). Streptozotocin-induced diabetes mellitus (STZ-DM), caused by the destruction of pancreatic β-cells and is similar to T1DM in human, is characterized by mild to moderate hyperglycemia, glucosuria, polyphagia, hypoinsulinemia, hyperlipidemia, and weight loss.…”
Section: Diabetic Modelmentioning
confidence: 99%
“…The rats in the control group were injected intraperitoneal with a single dose of 0.1M sodium citrate buffer (pH 4.5), while the rats in the DM group were injected intra-peritoneal with a single dose of citrate buffer containing 60mg/kg body weight of streptozotocin (Sigma Chemical Co., St. Louis, MO, USA). (Alkan et al, 2002;McCracken et al, 2006;Shyng et al, 2001;Tein et al, 1998) All animals were fed on standard Rodent diet (Rodent Diet CE-2; Japan Clea Inc., Shizuoka, Japan) with free access to water. Body weights, the presence of glucose in urine and blood glucose levels were recorded on day 0, 2, 7, 14, 21 and 28 after STZ injection.…”
Section: Inducing Diabetic Conditionmentioning
confidence: 99%